Advanced mucinous colorectal cancer: epidemiology, prognosis and efficacy of chemotherapeutic treatment - Ott, Claudia; Teufel, Andreas (Digestion, 2018)
Background: The clinicopathological significance of the mucinous subtype of colorectal cancer (CRC) remains controversial. As of today, none of the current guidelines differentiate treatment with respect to mucinous or nonmucinous cancer. Due to the lack of substantiated data, best treatment remains unclear and the mucinous subtype of CRC is usually treated along the lines of recommendations for adenocarcinoma of the colon. Methods: We investigated an East-Bavarian cohort of 8,758 patients with CRC. These included 613 (7.0%) patients with a mucinous subtype, who were analyzed for assessing their characteristics in clinical course and for evaluating the efficacy of common chemotherapy protocols. Results and Conclusion: Mucinous CRC was predominantly located in the right hemicolon; it was diagnosed at more advanced stages and occurred with preponderance in women. A higher rate of G3/4 grading was observed at diagnosis (all p < 0.001). An association of mucinous CRC with younger age at initial diagnosis, previously reported by other groups, could not be confirmed. Patients with mucinous stage IV colon cancer demonstrated poorer survival (p = 0.006). In contrast, no differences in survival were observed for specific stages I-III colon cancer. Stage-dependent analysis of rectal cancer stages I-IV also showed no differences in survival. However, univariable overall analysis resulted in significant poorer survival of mucinous compared to nonmucinous rectal cancer (p = 0.029). Also, combined analysis of all patients with mucinous CRC revealed poorer overall survival (OS) of these patients compared to nonmucinous CRC patients (median 48.4 vs. 60.2 months, p = 0.049) but notin multivariable analysis (p = 0.089). Chemotherapeutic treatment showed comparable efficacy regarding OS formucinous and nonmucinous cancers in both an adjuvant and palliative setting for colon cancer patients (p values comparing mucinous and nonmucinous cancers < 0.001-0.005).